2019
DOI: 10.1039/c8bm01333k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of redox-responsive doxorubicin and paclitaxel prodrug nanoparticles with microfluidics for selective cancer therapy

Abstract: Doxorubicin–paclitaxel prodrug nanoparticles with redox-responsive were synthesized to selectively inhibit cancer cells with reduced adverse drug effect to healthy cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…For covalent conjugation method, a lot of anticancer drugs have been investigated to prepare the amphiphilic drug-drug conjugates, including irinotecan-doxorubicin conjugate, 47,48 floxuridine-bendamustine conjugate, 49 irinotecan-HIF-1α conjugate, 50 methotrexate-CPT conjugate, 51 irinotecan-bendamustine conjugate, 52 irinotecan-chlorambucil conjugate, 22 gemcitabinechlorambucil conjugate, 22,53 CPT-floxuridine conjugate, 54 gemcitabine-CPT conjugate, [55][56][57] methotrexate-CPT conjugate, 58 methotrexate-doxorubicin conjugate, 58 CPTirinotecan conjugate, 59 irinotecan-enediyne conjugate, 60 doxorubicin-paclitaxel conjugate, 61 and floxuridinepseudolaric acid B conjugate. 62 Most of these amphiphilic drug-drug conjugates can directly assemble into nanoparticles in water for cancer therapy.…”
Section: Drug-drug Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For covalent conjugation method, a lot of anticancer drugs have been investigated to prepare the amphiphilic drug-drug conjugates, including irinotecan-doxorubicin conjugate, 47,48 floxuridine-bendamustine conjugate, 49 irinotecan-HIF-1α conjugate, 50 methotrexate-CPT conjugate, 51 irinotecan-bendamustine conjugate, 52 irinotecan-chlorambucil conjugate, 22 gemcitabinechlorambucil conjugate, 22,53 CPT-floxuridine conjugate, 54 gemcitabine-CPT conjugate, [55][56][57] methotrexate-CPT conjugate, 58 methotrexate-doxorubicin conjugate, 58 CPTirinotecan conjugate, 59 irinotecan-enediyne conjugate, 60 doxorubicin-paclitaxel conjugate, 61 and floxuridinepseudolaric acid B conjugate. 62 Most of these amphiphilic drug-drug conjugates can directly assemble into nanoparticles in water for cancer therapy.…”
Section: Drug-drug Conjugatesmentioning
confidence: 99%
“…62 Most of these amphiphilic drug-drug conjugates can directly assemble into nanoparticles in water for cancer therapy. Interestingly, Zhang et al 61 reported the preparation of doxorubicin-paclitaxel prodrug nanoparticles with microfluidics. Many of these nanodrugs showed synergistic anticancer efficacy and some of them even could overcome the multidrug resistance of tumor cells.…”
Section: Drug-drug Conjugatesmentioning
confidence: 99%
“…Nevertheless, direct applications of the antibody as a drug for oncotherapy may result in serious cytokine storm. To avoid this situation, proper drug delivery systems, such as nanoparticles [13][14][15][16][17][18][19], microparticles [20][21][22][23][24][25][26] or hydrogels [27][28][29][30][31][32][33] are employed for reducing drug toxicity and inhibiting the multi-drug resistance. However, the problems that come with these nano-carriers are the insufficient efficacy due to their short action time at tumor site, and the excessive systemic immune response because of the easy-spreading blood circulation; whereas the bulk delivery systems are not applicable for controllable drug release, substance exchange with outer environment, and flexible implantation since their relatively larger size and simple structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicines that respond to pH [11,12], temperature [13], light [14], redox state [15], magnetic elds [16,17], biomolecules [18], or combinations thereof have been developed and proved. The clinical success of nanoparticle-based therapy illustrates the power of this approach.…”
Section: Introductionmentioning
confidence: 99%